THE IMPACT OF PEER ASSESSMENT ON LEARNING MOTIVATION AMONG PHYSICAL EDUCATION STUDENTS - BĂLOI, Andrei-Iasmin; DOMILESCU, Gabriela-Ioana; ALMĂJAN, Bogdan (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2025)
This study explores the impact of peer assessment on learning motivation among students majoring in Physical Education and Sport. Conducted using a quasi-experimental design with pre-test and post-test evaluations, the research involved two groups (experimental and control) and measured intrinsic motivation, extrinsic motivation, amotivation, and perceptions of peer assessment. The findings revealed no statistically significant differences between the groups after the intervention. However, both groups exhibited a significant decline in intrinsic and extrinsic motivation, indicating a general decrease in motivation during the intervention period. The discussion highlights that, although existing literature supports the potential of peer assessment to enhance motivation, its effectiveness depends on contextual factors such as implementation method, perceived fairness, and motivational climate. The study underscores important theoretical and practical implications for integrating peer assessment in physical education, suggesting future research should focus on randomized designs, more diverse samples, and the long-term effects of peer assessment on learning motivation.